Milk production and nitrogen excretion of grazed dairy cows in response to plantain (Plantago lanceolata) content and lactation season - Thi Truong Nguyen; Soledad Navarrete; David Horne; Daniel Donaghy; Peter Kemp (Animal Bioscience)
Objective The study aimed to quantify milk production and urinary nitrogen (UN) excretion of dairy cows grazing pastures containing varying amounts of plantain (Plantago lanceolata) in different seasons, under a typical farm practice. Methods Four pasture treatments: perennial ryegrass (Lolium perenne) – white clover (Trifolium repens) (RGWC), RGWC + low plantain rate, RGWC + medium plantain rate, and RGWC + high plantain rate, were established in four adaptation areas (1 ha each) and 20 experimental plots (800 m2 each), and rotationally grazed by dairy cows over 14 grazing events during two lactation years. In each grazing (8 to 9 days), 60 or 80 Jersey-Friesian lactation cows were assigned to their pasture treatments, adapted to their pastures over the first six days, then each group of 15 or 20 cows were randomly allocated for grazing in five treatment plots over a two or three-day measurement period. Milk, urine, and faecal samples were collected from individual cows during the measurement period. Results The pasture treatments did not affect milk production, the yield and composition of milk solids, protein, fat, and lactose. However, cows grazing pastures containing between 17% and 28% dietary plantain reduced UN concentration by 15% to 27%, decreased UN excretion by 4% to 9%, and increased urine volume by 22% to 40%, compared to grazing the RGWC pasture. The change in UN concentration, and urine volume were associated with plantain proportion in the diet and were greater during late summer and autumn than during early summer. Conclusion Incorporating 17% to 28% dietary plantain with RGWC pastures can reduce the risk of nitrogen losses from pastoral systems, while maintaining the milk production of dairy cows.